SEJARAH PERKEMBANGAN AGAMA KATOLIK DI BAGANSIAPIAPI (1928-1942) - Rut Sontiara Simatupang; Bedriati Ibrahim; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is about "The History of the Development ofCatholicism in Bagansiapiapi (1928-1942)” . In 1930 Bagansiapiapi was dominated byethnic Chinese who were immigrants from China. Who are Buddhists and Confucians.In addition, there are also indigenous Bagansiapiapi people, namely Malay people whoare Muslim. The entry of Catholicism begin with the entry of the Neterland inBagansiapiapi. This research discusses how the development of Catholicism inBagansiapiapi. The research methodology used is historical research methods with theprocess of collecting data through documentation, interviews and literature study. Theresults denote that Catholicism can be accepted by ethnic Chinese who are immigrantsto Bagansiapiapi. The begin entry of Catholicism was dominated by ethnic Chinese whobecame the majority at that time. In addition, the role of missionaries who came fromthe Netherlands who paid attention to education by establishing a Netherland-Chineseschool (HCS) and the health by the construction of polyclinics and leprosy villages. In2020 the Catholics in Bagansiapiapi are dominated by the Batak and Javaneseethnicities.Key Words: Development, Catholic